2018
DOI: 10.1038/s41598-018-29752-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optical Coherence Tomography Angiography to Indocyanine Green Angiography and Slit Lamp Photography for Corneal Vascularization in an Animal Model

Abstract: Corneal neovascularization (CoNV) could be treated by novel anti-angiogenic therapies, though reliable and objective imaging tools to evaluate corneal vasculature and treatment efficacy is still lacking. Optical coherence tomography angiography (OCTA) –currently designed as a retinal vascular imaging system— has been recently adapted for anterior-segment and showed good potential for successful imaging of CoNV. However, further development requires an animal model where parameters can be studied more carefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…By shining a thin sheet of light into the eye, an in vivo stereoscopic evaluation of the pathological changes of the cornea, conjunctiva and other anterior segment tissues can be performed by SLB [9]. However, the limited magnification and poor spatial resolution of traditional SLB make it difficult to visualize more detailed pathological structures and perform accurate biometric measurements [10][11][12]. Fluorescein stain could stain stroma while leaving the intact epithelium with a specific fluorescein dye, thereby demarcating the location and area of the epithelial loss in ocular surface diseases, on a relative macro scale as well [13].…”
mentioning
confidence: 99%
“…By shining a thin sheet of light into the eye, an in vivo stereoscopic evaluation of the pathological changes of the cornea, conjunctiva and other anterior segment tissues can be performed by SLB [9]. However, the limited magnification and poor spatial resolution of traditional SLB make it difficult to visualize more detailed pathological structures and perform accurate biometric measurements [10][11][12]. Fluorescein stain could stain stroma while leaving the intact epithelium with a specific fluorescein dye, thereby demarcating the location and area of the epithelial loss in ocular surface diseases, on a relative macro scale as well [13].…”
mentioning
confidence: 99%
“…As a contactless and non-invasive procedure, OCTA has recently found clinical application, especially in ophthalmology, since it allows generation of high-resolution images of the perfusion of the anterior eye segment, choroid and retina. Several experimental and clinical studies have shown the reliability and validity of OCTA for monitoring microvascular perfusion of the eye [28][29][30][31] . In the present study, OCTA was used successfully to evaluate the sublingual microcirculation in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The first obvious application is the objective delineation and potentially quantification of corneal vascularisation (Figure ) . Importantly, OCT‐A of corneal neovascularisation has been validated against histology in animal models, whereas this has not been achieved with posterior segment OCT‐A. As the physiologically normal cornea is essentially avascular and receives oxygen from the air and the aqueous humour, pathological corneal vascularisation affects corneal transparency.…”
Section: Oct‐a Of the Anterior Segmentmentioning
confidence: 99%